Antiviral Properties of Silver Nanoparticles on a Magnetic Hybrid Colloid - Park, SungJun; Park, Hye Hun; Kim, Sung Yeon; Kim, Su Jung; Woo, Kyoungja; Ko, GwangPyo (Applied and Environmental Microbiology, 2014)
Silver nanoparticles (AgNPs) are considered to be a potentially useful tool for controlling various pathogens. However, there are concerns about the release of AgNPs into environmental media, as they may generate adverse human health and ecological effects. In this study, we developed and evaluated a novel micrometer-sized magnetic hybrid colloid (MHC) decorated with variously sized AgNPs (AgNP-MHCs). After being applied for disinfection, these particles can be easily recovered from environmental media using their magnetic properties and remain effective for inactivating viral pathogens. We evaluated the efficacy of AgNP-MHCs for inactivating bacteriophage ϕX174, murine norovirus (MNV), and adenovirus serotype 2 (AdV2). These target viruses were exposed to AgNP-MHCs for 1, 3, and 6 h at 25°C and then analyzed by plaque assay and real-time TaqMan PCR. The AgNP-MHCs were exposed to a wide range of pH levels and to tap and surface water to assess their antiviral effects under different environmental conditions. Among the three types of AgNP-MHCs tested, Ag30-MHCs displayed the highest efficacy for inactivating the viruses. The ϕX174 and MNV were reduced by more than 2 log 10 after exposure to 4.6 × 10 9 Ag30-MHCs/ml for 1 h. These results indicated that the AgNP-MHCs could be used to inactivate viral pathogens with minimum chance of potential release into environment.